Improving Supply Chain Performance Through Information Technology: An Integrative Approach - Novessro, Maskal Imran; Pratiwi, Nindya Pangestika; Yanti, Alma; Djatmiko, Wahyu Adji; Nainggolan, Nelly Farida Rodiana; Tannady, Hendy (Journal of Information System, Technology and Engineering, 2025)
In an era of complex disruption, information technology plays a critical role in improving supply chain performance through operational transparency, efficiency, and collaboration between partners. This study aims to explore the impact of IT on supply chain performance, focusing on technologies such as the Internet of Things (IoT), Radio Frequency Identification (RFID), and cloud-based platforms. A systematic literature review method was used to analyze data from relevant journals, with inclusion criteria including articles discussing the impact of IT on key performance indicators, such as supply chain flexibility, innovation, and resilience. The results showed that IT implementation provides significant benefits, including reducing inventory management errors by up to 30%, improving response to disruptions, and distribution efficiency. IT also supports collaboration through real-time information sharing, which drives product and process innovation. However, challenges such as high investment requirements, technology skills gaps, and data security risks remain major barriers to its implementation. A phased adoption strategy and intensive training for human resources are recommended to overcome these barriers.